Comparative Radiological Diagnostics of Acute Triangular Fibrocartilage Complex Injuries - Roman Pavić; Petra Margetić; Mirta Benšić; Dijana Hnatešen; Mario Kopljar; Karla Margetić (Acta Clinica Croatica, 2022)
The aim was to analyze patients with clinical diagnosis of triangular fibrocartilage complex (TFCC) lesion using standard x-ray, ultrasound, conventional magnetic resonance imaging (MRI) and MR arthrography (MRA); to evaluate the accuracy of MRA compared with MRI in the diagnosis of this lesion; and to evaluate ultrasound as a method of diagnosing TFCC lesion. We analyzed 72 patients (46 female and 26 male; age range, 22-61 years; mean age 37 years; 50 right and 22 left wrists) with suspected TFCC lesion with clinical examination, standard x-rays, and ultrasound. We confirmed patients with traumatic TFCC injury on MRI and MRA. Ultrasound found 13 lesions in 72 patients with suspected TFCC lesions. Conventional MRI found 66 and MRA 68 TFCC lesions. Ultrasound is useful for visualizing intra-articular effusion, soft tissue, bone surface, and for early detection of occult fractures. MRI is a better diagnostic modality, fully able to visualize the TFCC cartilage and ligaments. MRA is consistently and accurately able to visualize structural abnormalities of TFCC.